The Use of Vegetation Indices on Temporal Mangrove Condition: A Case Study on Timbulsloko and Bedono, Demak - Zahra Safira Aulia; Rudhi Pribadi; Muhammad Helmi (Jurnal Ilmiah Perikanan dan Kelautan)
Abstract